Verdade e arte a concepção ontológica da obra de arte no pensamento de Martin Heidegger - Rabello, Juliano (Editora Oficina Universitária, 2021)
The central objective of this book is to address the theme of art in Martin Heidegger. Linked to the question of the essence of truth, Heidegger's reflection on the work of art is elaborated from a resumption of the Greek expression Alétheia. In order to present this notion as a fundamental intuition that will guide Heidegger's philosophical path, the author passes through the developments of the "Fundamental Ontology" of Being and Time (1927) to the context of the turning point (Kehre) of his thought (1930), where the theme of art is situated. In this direction, it seeks to approach in the analyzed texts how Heidegger develops his reflections regarding this theme, mainly in the essay The origin of the work of art (1935-36), in which the philosopher presents, together with the question of the essence of language and poetry, the guiding notions of his ontological conception of the work of art, which, in turn, diverges from the traditional theories of Philosophical Aesthetics.